MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROYEK PEMBANGUNAN JAMBULUWUK HOTEL & RESORT PETITENGET - Bayu Dharma, Anak Agung; Adnyana Putera, I G. A; Parami Dewi, A. A. Diah (JURNAL SPEKTRAN; Vol 5 No 1 (2017): Vol. 5, No. 1, Januari 2017DO - 10.24843/SPEKTRAN.2017.v05.i01.p06, 2017)
Abstract : Work accidents that occur on the construction project will be one of the causes of the disruption or cessation of activities of the project work. The construction sector is the highest contributor to work accidents and occupational illness in Bali. Rampant construction of temporary lodging facilities or hotels in Bali can be one of the contributors to accidents. This study aims to determine the potential hazard and any dominant risk contained in a hotel development process as well as provides preventive measures to reduce such risks. In this research, the method used was descriptive qualitative. The risk of Occupational Health and Safety (K3) was identified through JSA (Job Safety Analysis). Questionnaire survey was carried out to get feedback from the experts regarding the potential hazards identified. The dominant category of risk assessment that was rated by the concept of ALARP (As Low As Reasonably Practicable). The research identified 45 of dominant risks contained in the phase of work structures including 43 risks classified as high risk such as : exposed to maneuver heavy equipment and vehicles, heavy equipment rolled because the excavated area slid down/ subsided, cross rope of Tower Crane disconnected / entangled on the operation, the charge fell from Tower Crane and as many as two risks were classified as very high risk (extreme risk) that is : exposed to maneuver mixer and swing Tower Crane over the edge area of the project. The risks tended to be sourced in the work environment factors and work equipment. In order to minimize the impact of K3 risks, it is necessary to conduct risk control, evaluation activities in a daily, weekly, monthly periodic, considering a safe distance hazard source from workers, setting working hours, scenario procedures of an emergency, as well as safe work through work instruction to remind the importance of working in a healthy and safe condition.
Keywords: risk management, occupational health and safety, JSA, K3 construction